Approaches towards social deprivation: Reviewing measurement methods - Świgost, Agnieszka (Bulletin of Geography. Socio-economic Series, 2017)
The phenomenon of social deprivation is highly diversified; hence there are a number of methods for measuring it. This article is a summary of a literature review concerning the methodology for calculating deprivation indices showing differences in research on deprivation. Reports, carried out on behalf of public administrations as well as academic articles from ten socially and economically developed countries, although diversified, were analysed. Partial indicators from the indices were classified into eight thematic groups representing different deprivation dimensions. A total of 166 partial indicators were analysed. Moreover, other methods of researching social crisis phenomena were discussed i.e. the indices employed by the UN and the USA. In the analysed countries, indicators of education and living conditions were considered most frequently while those relating to health and crime the least. The most common partial indicators are average levels of income, unemployment, overcrowding and education.